NBDE Part II Practice Analyses: An Overview. Issue 12 (1st December 2013) - Tsai, Tsung‐Hsun; Kramer, Gene A.; Yang, Chien‐Lin; Neumann, Laura M.; Chang, Shu‐Ren
Abstract : The Standards for Educational and Psychological Testing emphasize the importance of documenting and describing the procedures followed in developing valid test content. As a result, the Joint Commission on National Dental Examinations, the testing agency responsible for administering the National Board Dental Examination Part I and Part II, routinely communicates information about the validity of Part II to dental schools and other communities of interest. Since 2000, the content of Part II has been validated through the use of three practice analyses. This article provides an overview of these practice analyses, including procedures and findings. In general, the findings confirm that the content of Part II is valid in determining the qualifications of individuals seeking dental licensure.